(untitled) (Journal of Partial Differential Equations, 2003)
" In the paper, the existence and uniqueness of the generalized global solution and the classical global solution of the initial boundary value problems for the nonlinear hyperbolic equation u_tt + k_1u_xxxx + k_2u_xxxxt + g(u_xx)_xx = f(x, t) are proved by Galerkin method and the sufficient conditions of blow-up of solution in finite time are given."